Feasibility of Intersectoral Collaboration in Epidemic Preparedness and Response at Grassroots Levels in the Threat of COVID-19 Pandemic in Vietnam - Le, Huong Thi; Mai, Hue Thi; Pham, Hai Quang; Nguyen, Cuong Tat; Vu, Giang Thu; Phung, Dung Tri; Nghiem, Son Hong; Tran, Bach Xuan; Latkin, Carl A.; Ho, Cyrus S. H.; Ho, Roger C. M. (Frontiers in Public Health, 2020)
To effectively control the COVID-19 outbreak in later stages in Vietnam requires addressing the existing gaps in the national health emergency framework, consolidate and inform its structure, we conducted this study to evaluate the importance and collaborative mechanism between health and community service workers with intersectional organizations at grassroots levels in Vietnam. A cross-sectional, web-based survey was conducted from 12/2019 to 02/2020 on 581 participants (37 health workers, 473 medical students, and 71 community service workers). The Snowball Sampling technique was used to recruit participants. We used exploratory factor analysis to test the construct validity of the questionnaire measuring the perceived efficiency of involving community service workers in healthcare-related activities, and Tobit models to examine its associated factors. The results showed the importance of local organizations in epidemic preparedness and response at grassroots levels, with scores ranging from 6.4 to 7.1, in which, Vietnam Youth Federation played the most important role (Mean = 7.1, SD = 2.2). Of note, community service workers were viewed as performing well in health communication and education at agencies, schools, and other localities. Medical students perceived higher efficiency of involving community service workers in healthcare-related activities at grassroots levels as compared to health workers. We encourage the government to promote intersectoral collaboration in epidemic preparedness and response, giving attention to scale up throughout training as well as inter-district and inter-provincial governance mechanisms.